Prevalence of Risk Factors of Acute Coronary Syndrome in Erbil Cardiac Center: comparing ST-elevation with non ST-elevation Acute Coronary Syndrome - Omar Hama Radha Qader; Mariwan Saka (Advanced Medical Journal)
Background and objectives: Acute coronary syndrome is the leading cause of death all over the world, there are many different risk factors as important etiology for this acute condition, this syndrome has been studied in different countries with a variety of results.